PROVISION OF CLEAN WATER FOR DRINKING AND PURIFICATION FOR THE VILLAGERS CIBEUREUM-CISARUA BOGOR REGENCY - Roestamy, Martin (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2015)
Biological, water is one of resource that has tremendous benefits for human life on earth, humans carry a higher quality of life by using water. During its development, the needs access to clean water is recognized and established as one of the basic human needs as a human right, but in fulfillment precisely sometimes show some things that are not satisfactory, as injustice control and access to clean water, where constraints such as weak economic level impact to the limited access to water, not to mention social inequality factor in the pace of development which sometimes puts the weak economy become marginalized communities to benefit the development, no doubt also the fulfillment of access to clean water as a basic need that will affect to the quality of life.